Sistem Informasi Akademik Pada Sekolah MI Miftahuddiniyah Berbasis Web - Afandi, Dedi; Hadapi Akhbar, Ahmad; Isarianto; Rozikin, Zaenur (Jurnal SIGMA, 2023)
The world of education is currently developing very rapidly. In this rapid development, along with the development of technology and information that occurs. This very diverse technology and information requires quality improvements and mechanisms for the service sector to be more efficient, so that the Human Resources (HR) that have been produced from the world of education can make a contribution to the process of building the outside world in accordance with their expertise. When the data processing and academic data information system is running, it is still done manually so that it is possible to cause efficiency problems with time in the data processing process. To overcome these problems MI Miftahuddiniyah requires a web-based academic information system. The goal is to minimize errors and provide convenience to the school academics in processing data. The development method used in this information system is using the waterfall method, where the steps of this method begin with an analysis of system requirements, and continue with material collection, design, manufacture, testing (redesign if not appropriate) and system application. The results of this study are in the form of a website for the MI Miftahuddiniyah Academic Information System. The development of this Academic Information System is made in a web-based application that can make it easier for admins to process report data management, minimize errors and data loss because the processed data is stored in the database, and can speed up the process of inputting student grade data. Keywords:Web-Based Academic Information System with Waterfall Method, PHP, MySQL, SS